Split Hopkinson (Kolsky) bar design, testing and applications - Chen, Weinong; Song, Bo.; SpringerLink (Online service). (Boston, MA Springer US, 2011)
The authors systematically describe the general principles of Kolsky bars, or split Hopkinson bars, which are widely used for obtaining dynamic material properties. Modifications are introduced for obtaining reliable data. Specific experiment design guidelines are provided to subject the specimen to desired testing conditions. Detailed Kolsky-bar examples are given for different classes of materials (brittle, ductile, soft, etc) and for different loading conditions (tension, torsion, triaxial, high/low temperatures, intermediate strain rate, etc). The Kolsky bars used for dynamic structural characterization are briefly introduced. A collection of dynamic properties of various materials under various testing conditions is included which may serve as a reference database. This book assists both beginners and experienced professionals in characterizing high-rate material response with high quality and consistency. Readers who may benefit from this work include university students, instructors, R & D professionals, and scholars/engineers in solid mechanics, aerospace, civil and mechanical engineering, as well as materials science and engineering.
Electronic reproduction.
Keywords: Materials -- Dynamic testing; Mechanics -- Experiments; Electronic books